2016
DOI: 10.1083/jcb.201602002
|View full text |Cite
|
Sign up to set email alerts
|

A reverse signaling pathway downstream of Sema4A controls cell migration via Scrib

Abstract: Semaphorins are ligands for their receptors, plexins. In this study, Sun et al. show that a transmembrane semaphorin, Sema4A, transduces signals in a reverse manner to control migration of cancer and dendritic cells via the cell polarity protein Scrib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 90 publications
(114 reference statements)
0
38
0
Order By: Relevance
“…Similarly, in response to directional cues, MCF-10A epithelial cells require Scribble to recruit Rac1 and Cdc42 to the leading edge to form stable lamellipodial protrusions (Dow et al, 2007). A promigratory function for Scribble has also been shown in dendritic cells and certain cancer cell lines, acting downstream of the interaction of Plexin-B1 with its transmembrane receptor Sema4A (Sun et al, 2017). Here, it is suggested that the interaction with Sema4A leads to reduced binding of Scribble to β-PIX, with consequences for polarized Cdc42 and Rac activity (Sun et al, 2017).…”
Section: Scribble Also Regulates Cell Migration and Metastasismentioning
confidence: 99%
“…Similarly, in response to directional cues, MCF-10A epithelial cells require Scribble to recruit Rac1 and Cdc42 to the leading edge to form stable lamellipodial protrusions (Dow et al, 2007). A promigratory function for Scribble has also been shown in dendritic cells and certain cancer cell lines, acting downstream of the interaction of Plexin-B1 with its transmembrane receptor Sema4A (Sun et al, 2017). Here, it is suggested that the interaction with Sema4A leads to reduced binding of Scribble to β-PIX, with consequences for polarized Cdc42 and Rac activity (Sun et al, 2017).…”
Section: Scribble Also Regulates Cell Migration and Metastasismentioning
confidence: 99%
“…Moreover, another report showed that SEMA4A on the surface of immune cells engaged in trans with NRP1 expressed on Treg lymphocytes, promoting their immunosuppressive activity [41]. SEMA4A also contains an intracellular domain that can mediate reverse signaling cascades into dendritic cells, for instance controlling their migration [42]. The role of SEMA4A in cancer context is still unclear.…”
Section: Semaphorin 4amentioning
confidence: 99%
“…Enrichment analysis of the downregulated genes implicated GO term pathways predominantly involved in cell migration, cell motility, locomotion, and localization (Figure B). The genes comprising these GO terms include C5ar1 (a receptor for C5a, a known chemoattractant) as well as multiple genes associated with tumor metastasis ( Cmtm3, Nr4a1, Sparc, Tnf, Gpnb ) and with chemotaxis, adhesion, and cytoskeletal interactions ( Fermt3, Rhod, Cd151, Sema4a, Plxnd1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The gene array analyses performed on RNA derived from graft‐infiltrating mononuclear cells add to the literature by associating numerous genes previously shown to participate in chemotaxis, angiogenesis, adhesion, and cancer metastasis with C5aR1. Additional studies to be performed by our laboratory, among others, are required to test the specific hypothesis that these gene products, individually or together, are requisite intermediaries of C5a/C5aR1‐initiated Mreg chemotaxis.…”
Section: Discussionmentioning
confidence: 99%